Losada, Leandro, Marcelo T. de Alvear. Revolucionario, presidente y líder republicano, Buenos Aires, Edhasa, 364 pp. - San Martín, María Victoria (2017)
Fil: San Martín, María Victoria. Investigadora Independiente; Argentina